-6(u+5)^2=120

3 answers

-5 + or - 4i squareroot 5
-5 to both sides?
so what about the u?
in the parenthises with the five, what happens to that?
Take the (u+5)^2 and solve (u+5)(u+5)

that gives you -6(u^2-10u-25)=120

then distribute the -6

-6u^2-60u-150= 120 then subtract 120 from both sides

-6u^2-60u-270=0 then divide everythin by -6 giving you

u^2+10u+45=0 then use the quadratic formula
(-b +/- squareroot b^2 -4ac)/2a

then you will get the answer. If you don't know how to use the quadratic formula then let me know.